Effect of the natural sweetener, steviol glycoside, on cardiovascular risk factors: A systematic review and meta-analysis of randomised clinical trials. - Onakpoya, I; Heneghan, C (2014)
INTRODUCTION: Many different dietary supplements are currently marketed for the management of hypertension and diabetes, but the evidence for effectiveness is mixed. The objective of this systematic review was to critically appraise and evaluate the evidence for effectiveness of steviol glycosides (stevioside and rebaudioside A) on cardiovascular risk factors, using data from randomised clinical trials (RCTs). METHODS: Electronic searches were conducted in Medline, Embase, Amed, Cinahl and The Cochrane Library. We also searched Google Scholar, and hand searched the bibliography of retrieved full texts. The reporting quality of included studies was assessed using the Cochrane criteria. Two reviewers independently determined the eligibility, assessed the reporting quality, and extracted the data. RESULTS: Nine studies with a total of 756 participants were included. There was a variation in the reporting quality of included studies. Meta-analysis revealed a non-significant difference in systolic blood pressure between steviol glycoside and placebo, mean difference (MD): -2.98 mm Hg (-6.23 to 0.27). Significant reductions in diastolic blood pressure and fasting blood glucose were observed. There was no significant effect on blood lipid profile. Heterogeneity was significant. Adverse events included abdominal fullness, epigastric pain, and dizziness. CONCLUSION: The evidence from published RCTs suggests that stevioside may generate reductions in blood pressure and fasting blood glucose. The sizes of the effects are small, and the substantial heterogeneity limits the robustness of any conclusions. Rebaudioside A does not appear to have any significant effects on blood pressure or cardiovascular risk factors. Available clinical trials vary in design and reporting quality, and some are characterised by inadequate sample sizes. In addition, the participants in most of the trials have high cardiovascular risk. Further clinical trials and regulatory assessments are warranted.